Diversity of medicinal plants in homegardens in Tanjung Julu village, North Sumatra, Indonesia - Silalahi, Marina (International Journal of Biological Research, 2016)
Background: The homegardens is a landscape which rich of plants diversity, so it have been used by human to supply of needs.Objective: To documention the medicinal plants in homegardens by local communities in Tanjung Julu village.Methods: the research conducted through ethnobotany approach. We interviwed to 30 informants and explored the 30 homegardens in Tanjung Julu village at August-December 2012.Results: A total 63 the medicinal plants species belonging to 48 genera and 29 families is reported with ethnomedicinal uses to curing the 20 diseases.Those that is used mostly belong to Zingiberaceae (11 species), Rutaceae (8 species), Euphorbiaceae (6 species),and Asteraceae (5 species). The medicinal plants in homegardens are economic commodities (18 species), vegetable (11species), and ornamental (9 species).Conclusions: The medicinal plants in homegardens by local communities in Tanjung Julu villages for subsistence of local households, significantly contribute to conservation of biodiversity.Â